Development of a child's moral module: A Design and Development Research (DDR) - Nur Adillah Ramly; Abdul Halim Masnan (Universitas Serambi Mekkah, 2024)
This study is a developmental study with the specific aims of explaining approaches in the development of child moral education modules. Currently, the Malaysian Ministry of Education is focusing on initiatives to enhance human capital in line with the Malaysian Education Development Plan 2013-2025. The Ministry of Education is committed to developing children holistically in a comprehensive and integrated way to realise a balanced and harmonious human being in intellectual, spiritual, emotional, and physical terms based on faith and obedience to God. In this connection, the paper suggests a design and development study (DDR) based on a multi-method approach. Using DDR, the research will go through three phases and employ a variety of research methods in every phase. The participation of research participants from expert groups and user groups can provide diverse input and take into account the needs of modules in the Malaysian context.